Religious Education and Eco-Theology: Reorienting Spirituality toward the Ecological Crisis - Lailatul Sakdiah; Ulyan Nasri; Saeful Gani; Abdul Halim; Eklis Dinika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study explores the integration of eco-theology within Islamic Religious Education (IRE) as a means to reorient spirituality in response to the current ecological crisis. The main problem addressed is the gap between religious understanding and environmental awareness among learners, which contributes to the lack of ecological ethics in Muslim communities. The objective of this research is to formulate a conceptual framework that connects Islamic theological values—such as tawḥīd (divine unity), khilāfah (stewardship), and amānah (moral responsibility)—with ecological consciousness through IRE. The study employs a qualitative-descriptive approach with literature analysis, drawing on classical Islamic sources and contemporary eco-theological discourses. The findings indicate that eco-theology can serve as a transformative foundation for IRE, promoting a holistic spirituality that integrates faith, ethics, and environmental care. The conclusion emphasizes that reorienting Islamic spirituality through eco-theological principles encourages sustainable living and strengthens moral responsibility toward the environment.